The Links Between Teachers’ Bodily Involvement and the Professional Development of Physical Education Novice Teachers: Exploratory Study - Ottet, François; Méard, Jacques (Swiss Journal of Educational Research, 2018)
The body of the teacher is not very present in teacher education issues. The exploratory study presented in this paper is based on the theoretical framework of the «clinic of activity» (Clot, 2008; Leontiev, 1976; Vygotski, 1930/1998) and combines the observation of classroom videos recordings and auto-confrontation interviews with two physical education novice teachers. The aim is to point out the links between teachers’ bodily involvement and their professional development. The results show that, in their activity, bodily operations participate in the professionnal development of the teachers, following the auto-confrontation interviews with the researcher. These initial results prompt many assumptions about a better understanding of «how a novice learns the profession of teacher» in order to improve vocational training practices and strengthen the health of the person at work.